Islamic Education Strategy for Children Without Parental Care in Islamic-Based Orphanages - Moh. Nasihin (IAIN Batusangkar, 2024)
This study aims to analyze Islamic education strategies applied in the upbringing of children in orphanages without biological parents. This research used a qualitative approach with field method, collecting data through interview, observation, and documentation study. The findings showed that the Semarang Muhammadiyah Orphanage has adopted proactive steps in strengthening Islamic education for children, focusing on holistic planning, implementation, and evaluation. They consistently update educational curricula and policies to accommodate the needs and development of learners. This approach not only enhances the learning experience, but also ensures the relevance and effectiveness of Islamic education in guiding the development of children in orphanages. The results described positive changes in attitudes and behaviors in foster children, such as increased learning motivation, tolerance, and love for the Quran. This research makes an important contribution in the understanding of Islamic education in orphanages and its implications for the development of children who do not have biological parents.